Changes in soil microbial population and biochemical properties of undisturbed and disturbed secondary forests converted to oil palm- cultivated area in Belaga, Sarawak, Malaysia - Mohd Nawar, Nur Hanani Hanis (2018)
Changes in microbial populations and biochemical activities can be affected by changes in the soil physical and chemical properties of soils. Assessment of the properties of soil in Belaga, Sarawak studies were conducted with the following objectives; i) to determine the populations of bacteria, actinomycetes, fungi and functional microbes (phosphate solubilizing bacteria and nitrogen-fixing bacteria) from secondary forests (BS1 and BS2) and oil palm cultivated areas in Belaga, Sarawak at different sampling periods, ii) to determine the changes in the biochemical , physico- chemical properties of soils in the three areas, iii) to determine the soil degradation indices in comparisons with secondary forests soil (BS1 and BS2) and oil palm cultivated areas and iv) to determine relationships between the changes in microbiological properties and the soil physico-chemical properties in secondary forests (BS1 and BS2) and oil palm cultivated areas. Samples of soils were obtained at 0-15 cm and ten replications were made in three different areas namely, undisturbed secondary forests (BS1), disturbed secondary forest (BS2) and oil palm cultivated area (OP) at three different sampling times (June 2012, January 2013, June 2013). A spread plate technique was used to determine the populations of microbes. Soil microbial biomass carbon (MBC), fluorescein diacetate assay (FDA) hydrolysis, β-glucosidase activity assay, urease activity assay, phosphatase activity assay, dehydrogenase assay were carried out to observed changes in biochemical properties of the soils. Results showed that microbial populations were significantly affected by location and time of sampling. Oil palm area showed the highest populations of bacteria (6.57 Log10 cfu g⁻¹) and fungi (5.57 Log10 cfu g⁻¹) in June 2013. Population of phosphate-solubilizing bacteria was consistently low in oil palm area compared to that in secondary forests (BS1 and BS2) in all sampling times. Oil palm area demonstrated consistently the lowest MBC in June 2012 and January 2013. The area also showed the lowest FDA (4.72 µg g⁻¹) in June 2012, whilst phosphatase (4265 ug pnp g soil⁻¹ hr⁻) in January 2013. Most soil properties responded to the different locations and were time dependent. There were strong effects of location, time and interactions of location and time in actinomycetes populations, MBC, moisture content and total C. Use of soil deterioration index showed that soils deteriorated severely (DI=-239.7 and -274.5) under oil palm cultivated area when compared to secondary forests (BS1 and BS2 respectively) and gradually recovered to positive values (DI= +16.6 and +4.9). This study indicated that oil palm cultivated area is resilience, where the soil has the ability to recover from perturbation. There were significant correlations amongst the soil properties indicating their interactions in sustaining the soil quality.